Community Participation in The Development of The Silokek Geopark, Silokek Village, Sijunjung Regency - Rexsi Rexsi; Ahmad Hidayah (LPPM Universitas PGRI Sumatera Barat, 2024)
This study examines community participation in the development of Geopark Silokek in Nagari Silokek, Sijunjung District, Sijunjung Regency. The research is motivated by the great potential of Geopark Silokek as an internationally valuable geological-based tourism site and as an opportunity to improve the welfare of local communities. A qualitative approach was employed with data collected through observation, interviews, and document analysis. Research informants consisted of community leaders, the village head, Geopark Silokek management, and local residents directly involved in the development of the area. Data were analyzed using Miles and Huberman’s interactive model. The findings reveal that community participation is manifested in three main forms: participation in ideas (contributing suggestions), participation in labor (collective work and field activities), and participation in resources (financial and material support). However, according to Arnstein’s A Ladder of Citizen Participation, the level of participation remains at the tokenism stage, particularly informing and consultation, which indicates that community involvement has not yet significantly influenced strategic decision-making. This study recommends enhancing community capacity and establishing formal institutions that promote higher levels of participation, namely partnership and citizen control, in order to ensure the sustainability of Geopark Silokek while maximizing its economic, social, and environmental benefits for the local community.